Optimisation of Formulation for the Manufacturing of Soy Fortified Shrikhand - Alam, Tanweer (Indian Journal of Dairy Science, 2016)
Shrikhand is an indigenous, traditional and fermented dairy dessert of India. The present investigation was carried out to optimise the process of manufacturing of soy fortified shrikhand. Soymilk, cane sugar and yoghurt culture (Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus) were the variables studied by employing the 3-factors Central Composite Rotatable Design. The formulation with 24.5% soymilk, 30% cane sugar and 3% yoghurt culture for soy fortified shrikhand was found highly suitable. The desirability index of optimised soy fortified shrikhand was 0.721 respectively.